Pengembangan Sistem Informasi Portal Banyuwangi Festival Berbasis Website Menggunakan Metode Rapid Application Development (RAD) - Wahyu Putra Adi Permana; Nurudin Santoso; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Banyuwangi Regency annually organizes a series of events entitled Banyuwangi Festival and it first held in 2012 with a total of 10 events, and now it is reaching 99 events. However, many problems must be faced by the organizers, for example, in 2016 there was a ticket forgery incident by an irresponsible person at the Banyuwangi Beach Jazz Festival. That incident happened due to the absence of a centralized system in the ticket reservation process at each event. Nowadays, web information systems and portals can help to integrate specific applications such as business intelligence, e-commerce or other application service providers. That ease was then integrated with the Banyuwangi Festival so that the BFEST website was developed, which could help organizers in festival management and ticket reservations more safely and centrally. The system was developed using the Rapid Application Development (RAD) method with needs analysis done twice and then produce 34 functional needs and one non-functional needs, then it was implemented using the PHP programming language in the CodeIgniter framework. This system has been tested with the white box testing method for unit and integration test and black-box testing for validation test which produces 45 test cases with 100% valid results, compatibility testing for non-functional requirements using SortSite tools and proven the system can run on several websites browser or mobile browser. Keywords: Banyuwangi festival, ticket reservation, management, website